DIGITAL EDUCATIONAL RESOURCES IN TEACHING FUTURE INFORMATICS TEACHERS TO CREATE IOT DEVICES - Turashova, Sh.; Seiduali, K.; Bazarbayeva, U.; Urazgaliyeva , Sh.; Yersin, M. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The Internet of Things (IoT) today is not just a technological trend, but a reality that is rapidly changing our lives. Cisco predicts that by 2030, the number of connected devices in the world will increase and reach 500 billion. This means that IoT will become an integral part of the future and the demand for IoT specialists will grow steadily. In this regard, preparing the younger generation for life in the IoT world is becoming a critically important task. The inclusion of IoT issues in the school’s computer science curriculum is an important step towards developing the necessary knowledge and skills for students. However, for the successful implementation of this program, it is necessary to provide schools with competent informatics teachers with not only theoretical knowledge, but also practical skills in the field of IoT. This will ensure high-quality education for students, prepare them for life in the IoT world and contribute to the development of this promising area of technology. To improve the effectiveness of teacher training, it is advisable to use modern teaching methods and digital educational resources. However, an analysis of existing scientific and methodological research in the field of teaching Internet of Things technology allows us to note an objectively small number of works devoted to the training of future informatics teachers in the field of IoT, especially in modern conditions of digitalization of education. The purpose of this study is to develop and test a model for teaching future informatics teachers how to create IoT devices as part of interdisciplinary projects based on modern digital educational resources. Research results: as part of an interdisciplinary IoT-based project, an automatic watering system for indoor plants was developed, the most effective digital educational resources and a learning model for creating and developing this IoT device were identified and developed using them. The degree of student satisfaction with the learning process of creating IoT devices using digital educational resources was assessed.